2014
DOI: 10.1080/07448481.2013.856914
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Self-guided, Home-Based Intervention to Improve Condom Use Among Young Men Who Have Sex With Men

Abstract: This pilot study supports an expanded trial of this intervention with MSM at high-risk of acquiring human immunodeficiency virus/sexually transmitted infections (HIV/STIs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 16 publications
(13 reference statements)
0
43
0
Order By: Relevance
“…[26] Interventions and health promotion programs that improve condom-use must focus on appropriate and consistent use. [27] Fortunately, we found that men who reported intentional consistent condom-use as a prevention strategy had four times greater odds of condom-use at the event-level. Condoms provide prevention for many STIs, but the TasP- and HAART-related attitudes and seroadaptive practices of men with lower odds of condom-use in our study reflect intentional consideration to reduce their possibility of acquiring HIV, potentially without (equal) concern for other STIs.…”
Section: Discussionmentioning
confidence: 81%
“…[26] Interventions and health promotion programs that improve condom-use must focus on appropriate and consistent use. [27] Fortunately, we found that men who reported intentional consistent condom-use as a prevention strategy had four times greater odds of condom-use at the event-level. Condoms provide prevention for many STIs, but the TasP- and HAART-related attitudes and seroadaptive practices of men with lower odds of condom-use in our study reflect intentional consideration to reduce their possibility of acquiring HIV, potentially without (equal) concern for other STIs.…”
Section: Discussionmentioning
confidence: 81%
“…water-based lubricants, silicon-based lubricants). Thus, condom interventions such as the Kinsey Institute Homework Intervention Strategy (KIHIS) 17,18 may benefit men experiencing CAEP as it attends to some of the most commonly cited CAEP attributions: sensation loss, application distraction, condom fit and feel and condom application skills. KIHIS is a self-guided home-based intervention, which encourages men to practice applying, using and removing a variety of condoms and condom-safe lubricants alone in a ‘low-pressure’ sexual situation.…”
Section: Discussionmentioning
confidence: 99%
“…Following completion of screening (Stage 2), five studies met all the inclusion criteria: studies that tested and reported outcome measures representing aspects of condom use fit and feel. [15][16][17][18][19] Characteristics of included studies…”
Section: Resultsmentioning
confidence: 99%